2001
DOI: 10.3168/jds.s0022-0302(01)74489-x
|View full text |Cite
|
Sign up to set email alerts
|

Case-Control Study of Risk Factors for Clinical Mastitis in Postpartum Dairy Heifers

Abstract: A case-control study was carried out to evaluate risk factors for clinical mastitis occurring in dairy heifers between 1 and 14 d postpartum. Case and control heifers were matched on herd; the control was the heifer that calved closest in time, before or after, the particular case. Data were analyzed by conditional logistic regression. The final multivariate model included 339 case-control pairs. Blood in the milk, udder edema, teat edema, and milk leakage, all recorded at the time of parturition, were signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
52
1
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 18 publications
3
52
1
2
Order By: Relevance
“…In particular, the number of CD8 + T cell decreased at week 1 in the PID cows. This observation was similar to that of a previous result reporting lower peripheral CD8 + T cells in the first 50 days after delivery [21]. CD8 + T cells have been demonstrated to increase over time in postpartal women, and there is also an increase in cytotoxic activity in early postpartal term [19].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In particular, the number of CD8 + T cell decreased at week 1 in the PID cows. This observation was similar to that of a previous result reporting lower peripheral CD8 + T cells in the first 50 days after delivery [21]. CD8 + T cells have been demonstrated to increase over time in postpartal women, and there is also an increase in cytotoxic activity in early postpartal term [19].…”
Section: Discussionsupporting
confidence: 92%
“…Many cases of PID occur within the first 2 weeks after calving [21]. It has been suggested that depression of leukocyte function during the periparturient period contributes to the susceptibility to infectious diseases in dairy cows, but the leading factors causing immune suppression have not been fully investigated.…”
mentioning
confidence: 99%
“…Heifer mastitis is considered as a condition which is discrete from mastitis in older cows and has a different presentation (Valde et al 2004) and distinctive features (Waage et al 2001;Alekish and Kenyon 2006;Compton and McDougall 2008;Godden et al 2008;De Vliegher et al 2012).…”
mentioning
confidence: 99%
“…Such a choice is recommended [55] and carried out for genetic studies [23,42,43,52,53,60,67,70,80]. According to the same approach, the expression of this dichotomous response is sometimes limited to a subperiod of the lactation: from 7 days before calving to 7 days after calving [66], the 5 first days after calving [19], the first 14 days [73,82], the first 30 days [7,20,74], the first 60 days [6], the first 100 days [18], or even a calendar year instead of the lactation [79]. The International dairy Federation recommends considering the 30 days before calving for primiparous animals [50].…”
Section: Solutions For Within Lactation Dependencementioning
confidence: 99%
“…This takes a potential overdispersion into account [75]. This is also possible through a case-control survey, by pairing a CMAST case with a within herd control, to use a single lactation per animal and define a dichotomous response for the lactation in order to minimise the different dependence problems [82]. But when using these methods, the numbers of analysed statistical units are sharply decreased and consequently it is not reasonable to accurately evaluate the studied factors.…”
Section: At the Lactation Levelmentioning
confidence: 99%